PET Neuroimaging: Insights on Dystonia and Tourette Syndrome and Potential Applications - Alongi, Pierpaolo; Iaccarino, Leonardo; Perani, Daniela (Frontiers in Neurology, 2014)
Primary Dystonia (pD) is a movement disorder characterized by sustained or intermittent muscle contractions causing abnormal, often repetitive, movements, postures, or both. Gilles de la Tourette Syndrome (GTS) is a childhood-onset neuropsychiatric developmental disorder characterised by motor and phonic tics, which could progress to behavioural changes. GTS and obsessive-compulsive disorders (OCD) are often seen in comorbidity, also suggesting a possible overlap in the pathophysiological bases of these two conditions. PET techniques are of considerable value in detecting functional and molecular abnormalities in vivo, according to the adopted radioligands. For example, PET is the unique technique that allows in vivo investigation of neurotransmitter systems, providing evidence of changes in GTS or pD. For example, presynaptic and postsynaptic dopaminergic studies with PET have shown alterations compatible with dysfunction or loss of D2-bearing neurons, increased synaptic dopamine levels, or both. Measures of cerebral glucose metabolism with 18F-fluorodeoxyglucose (18F-FDG PET) are very sensitive in showing brain functional alterations as well. 18F-FDG PET data have shown metabolic changes within the cortico-striato-pallido-thalamo-cortical and cerebello-thalamo-cortical networks, revealing possible involvement of brain circuits not limited to basal ganglia in pD and GTS. The aim of this work is to overview PET consistent neuroimaging literature on pD and GTS that has provided functional and molecular knowledge of the underlying neural dysfunction. Furthermore we suggest potential applications of these techniques in monitoring treatments.